Towards understanding the anticipated customer benefits of digital water metering. Issue 3 (16th March 2021) - Monks, Ian Robert; Stewart, Rodney A.; Sahin, Oz; Keller, Robert J.; Prevos, Peter
ABSTRACT: Research into the benefits of digital water metering (DWM) identified many benefits that were previously unrevealed in the literature. Many benefits are tangible and more easily quantified. Others, like a possible change in customer satisfaction (CS), are not. The objective of this study was to quantify any potential changes to CS from switching from conventional meters to DWM. The findings of a questionnaire survey of 178 customers determined a current average-CS score of 5.8 (0 (low) to 10 (high) scale); positive shifts in CS levels to individual DWM benefits of between 0.4 and 3.0; and, we demonstrated a prototype CS change prediction model that DWM implementation would derive a long-term CS step-change. The developed survey measurement items will benefit water utilities seeking to ascertain the benefits of DWM. The study will be of interest to researchers and water industry practitioners measuring CS and those developing business cases for DWM projects.